Pressure, Opportunnity, Rationalization, dan Capability terhadap Terjadinya Fraud : Studi di Salah Satu Dinas Propinsi Sulawesi Selatan - Nurwahyuni, Nurwahyuni (Politeknik Ganesha Medan, 2024)
This study examines the influence of Pressure, Opportunity, Rationalization, and Capability on Fraud within a department in South Sulawesi Province over two months, from December to January 2022. The department's entire staff constitutes the study population, with a saturated sampling method employed to ensure a representative sample. Field research methodology was utilized, employing quantitative data collection through questionnaire surveys. Data analysis was conducted using multiple linear regression with the assistance of statistical software.The results indicate that Pressure (Opportunity), Opportunity, Rationalization, and Capability significantly impact Fraud. The results indicate that Pressure (Opportunity), Opportunity, Rationalization, and Capability significantly impact Fraud. Practical recommendations for the study's subject include; conducting training on work ethics, stress management, and understanding of fraud prevention; implementing clear and stringent anti-fraud policies; enhancing communication and transparency throughout the organization; strengthening internal supervision mechanisms and fostering a work culture that values integrity and ethics.